Metabolomic profiles of preterm small-for-gestational age infants - Koh Okuda; Nobuhiko Nagano; Kimitaka Nakazaki; Kengo Matsuda; Wataru Tokunaga; Kazumasa Fuwa; Ryoji Aoki; Aya Okahashi; Ichiro Morioka (Pediatrics and Neonatology)
We aimed to characterize the metabolomic profiles in preterm small-for-gestational age (SGA) infants using cord blood. We conducted a gestational age (GA)-matched case-control study that included 30 preterm infants who were categorized into two groups: SGA infants, with a birth weight (BW) < 10th percentile for GA (n = 15) and non-SGA infants, with BW ≥ 10th percentile for GA (n = 15). SGA infants with chromosomal or genetic abnormalities were excluded. At birth, the umbilicus was double-clamped, and the cord blood was sampled from the umbilical vein. Metabolomic analyses were performed using capillary electrophoresis time-of-flight mass spectrometry. The median GA at birth was not significantly different between the two groups [SGA, 32 (26–36) weeks; non-SGA, 32 (25–35) weeks; p = 0.661)]. Of the 255 metabolites analyzed, 19 (7.5%) showed significant differences between SGA and non-SGA infants. There were significant reductions in the carnosine, hypotaurine, and S-methylcysteine levels in SGA infants as compared to non-SGA infants (p < 0.05). Carnosine was correlated with gestational age, BMI before pregnancy, body weight gain during pregnancy (p = 0.002, p = 0.023, and p = 0.020, respectively). In conclusion, preterm SGA infants have low levels of cord blood antioxidative- and antiglycation-related metabolites, making them vulnerable to oxidative stress.